Glycan-Functionalized Microgels for Scavenging and Specific Binding of Lectins - Jans, Alexander; Rosencrantz, Ruben R; Mandić, Ana D; Anwar, Naveed; Boesveld, Sarah; Trautwein, Christian; Moeller, Martin; Sellge, Gernot; Elling, Lothar; Kuehne, Alexander J. C (Biomacromolecules, 2017)
Lectins are proteins with a well-defined carbohydrate recognition domain. Many microbial proteins such as bacterial toxins possess lectin or lectin-like binding domains to interact with cell membranes that are decorated with glycan recognition motifs. We report a straightforward way to prepare monodisperse and biocompatible polyethylene glycol microgels, which carry glycan motifs for specific binding to lectins. The sugar-functionalized colloids exhibit a wide mesh size and a highly accessible volume. The microgels are prepared via drop-based microfluidics combined with radical polymerization. GSII and ECL are used as model lectins that bind specifically to the corresponding carbohydrates, namely, GlcNAc and LacNAc. LacNAc microgels bind ECL with a high capacity and high affinity (K d ≈ 0.5 to 1 μM), suggesting multivalent binding of the lectin to the LacNAc-decorated flexible microgel network. Glycan-functionalized microgels present a useful tool for lectin scavenging in biomedical applications.